#2**0 **

{4 x = 6 - 2 y | (equation 1)

x = y + 7 | (equation 2)

Express the system in standard form:

{4 x + 2 y = 6 | (equation 1)

x - y = 7 | (equation 2)

Subtract 1/4 × (equation 1) from equation 2:

{4 x + 2 y = 6 | (equation 1)

0 x - (3 y)/2 = 11/2 | (equation 2)

Divide equation 1 by 2:

{2 x + y = 3 | (equation 1)

0 x - (3 y)/2 = 11/2 | (equation 2)

Multiply equation 2 by 2:

{2 x + y = 3 | (equation 1)

0 x - 3 y = 11 | (equation 2)

Divide equation 2 by -3:

{2 x + y = 3 | (equation 1)

0 x+y = (-11)/3 | (equation 2)

Subtract equation 2 from equation 1:

{2 x+0 y = 20/3 | (equation 1)

0 x+y = -11/3 | (equation 2)

Divide equation 1 by 2:

{x+0 y = 10/3 | (equation 1)

0 x+y = -11/3 | (equation 2)

Collect results:

**Answer: | x = 10/3 and y = -11/3**

Guest May 27, 2017